Analysis of Bone-Cartilage-Stromal Progenitor Populations in Trauma Induced and Genetic Models of Heterotopic Ossification. (18th May 2016) - Agarwal, Shailesh; Loder, Shawn J.; Sorkin, Michael; Li, Shuli; Shrestha, Swati; Zhao, Bin; Mishina, Yuji; James, Aaron W.; Levi, Benjamin
Abstract: Heterotopic ossification (HO), the formation of extra-skeletal bone in soft tissues, is a pathologic process occurring after substantial burns or trauma, or in patients with type I bone morphogenetic protein (BMP) receptor hyperactivating mutations. Identifying the cells responsible for de novo bone formation during adulthood is of critical importance for therapeutic and regenerative purposes. Using a model of trauma-induced HO with hind limb Achilles' tenotomy and dorsal burn injury and a genetic nontrauma HO model ( Nfatc1-Cre/caAcvr1 fl/wt ), we demonstrate enrichment of previously defined bone-cartilage-stromal progenitor cells (BCSP: AlphaV+/CD105+/Tie2−/CD45−/Thy1−/6C3−) at the site of HO formation when compared with marrow isolated from the ipsilateral hind limb, or from tissue of the contralateral, uninjured hind limb. Upon transplantation into tenotomy sites soon after injury, BCSPs isolated from neonatal mice or developing HO incorporate into the developing lesion in cartilage and bone and express chondrogenic and osteogenic transcription factors. Additionally, BCSPs isolated from developing HO similarly incorporate into new HO lesions upon transplantation. Finally, adventitial cells, but not pericytes, appear to play a supportive role in HO formation. Our findings indicate that BCSPs contribute to de novo bone formation during adulthood and may hold substantial regenerative potential.